Comparison Of Number Of Teeth Lost In Periodontitis And Dental Caries In Age Group Of 30-60 Years. - PAUL, RACHEL; RAMAMURTHY, JAIGANESH; GURUNATHAN, DEEPA (The journal of contemporary issues in business and government, 2021)
Tooth loss can have profound effects on the individual< hence the prevention and treatment of the etiology of tooth loss is very important. The aim of the study is to compare the number of teeth lost due to periodontitis and dental caries in the age group of 30-60 years of age. Data was reviewed and analysis of the data of 110 patients were done. The data collected was from patients visiting the OP department, the data was then tabulated and statistical analysis was done in SPSS statistical analysis by IBM and the results were obtained. Out of 110 patients that were studied, 54.54% were female subjects and 45.45% were male subjects. The most common reason for extraction was found to be due to dental caries. The overall age group that underwent tooth extraction were 32-48 years with a gender predilection of females. Awareness programs must be initiated for various oral hygiene maintenance focusing on the prevention and the treatment of oral diseases.